ZONA LAYAK TAMBANG BAHAN GALIAN NON-LOGAM KECAMATAN PAMONA, KABUPATEN POSO, SULAWESI TENGAH - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2013)
Research at the Poso river Tentena – Sulewana segmen and Meko river, North Pamona district and West Pamona District, Poso regenc, Central Sulawesi Province. Rock there research area is river alluvial with the potential mining are sand and rock boulders, the mechanical laboratory of rock boulders of point load test result 207,005 – 744,797 Kg/Cm square, fullselment required for building material. Environmental condition of Poso river there are infrastructure for people housing, road of Poso – Tentena (Trans Sulawesi) and Poso Hydroelectric Power at the Sulewana village and the bridge, Meko river there are people housing and the bridge of Tentena Pendolo, and the forest and the many people garden. At the Poso river Tentena – Sulewana segmen sand can mine but the water level of river much be constant the water level of river much be constant until save the Poso Hydroelectric Power, at the Poso lake sand mining is problem with use the sump machin of sand until 20 meters depth, means the lateral pressure is not save to lake wall and to bellow the safety factor from 1,25 to 1,00 is critical condition, if there little tremble is sliding. At the Meko River there are bridge facility of road Tentena – Pendolo much be not disturb.